Pre-service Teachers' Perception of Renewable Energy Sources: A Case Study of Düzce University - Genç, Murat; Durak, Benzegül (Universitas Pendidikan Indonesia, 2023)
This research was conducted to examine pre-service teachers’ perception of renewable energy sources, tendency to use renewable energy and opinions about the future use of renewable energy sources and to investigate whether they have basic knowledge about renewable energy sources. To this end, the Renewable Energy Perception Scale, a 5-point Likert scale, was administered to a total of 755 pre-service teachers in the Science Teaching and Primary Teaching Departments in the Education Faculty of Düzce University. The scale has three sub-dimensions, namely “Renewable Energy Knowledge”, “Renewable Energy Future Vision”, and “Renewable Energy Tendency”. In the whole scale and its sub-dimensions of “Renewable Energy Knowledge” and “Renewable Energy Tendency”, it was found that the pre-service primary teachers had a statistically significantly better perception of renewable energy sources than the pre-service science teachers. Also, younger participants were found to have a statistically significantly better perception in the “Renewable Energy Tendency” sub-dimension. There is a statistically significant gender-based difference in the “Renewable Energy Future Vision” sub-dimension. On the other hand, no significant gender-based difference was found for the whole scale and the other sub-dimensions. This study shows the importance of examining pre-service teachers’ perception of renewable energy in terms of their better teaching these sources to their future students.